Molecular dissection of two Pakistani families segregating Leukocyte Adhesion Deficiency Type-I - Farzana Majeed; Atteaya Zaman; Saadia Moazzam; Muhammad Zeeshan Anwar; Muhammad Akram Shahzad; Momin Iqbal; Syed Irfan Raza (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Leukocyte adhesion deficiency (LAD1) is an autosomal recessive type of inherited disorder caused by total or partial deficiency of CD18 expression. LAD1 is characterized by recurrent bacterial and fungal infections, in some cases delayed umbilical cord separation, delayed wound healing due to blockade in leukocyte migration to site of inflammation and infection. The present study involves genetic analysis of two unrelated families suffering from LAD1.METHODOLOGY: In the present study, two separated and unrelated Pakistani families are included suffering from Leukocyte Adhesion Deficiency type -1 (PAD1). After detailed clinical evaluation, whole blood samples were collected from patients, parents and available healthy siblings. Genomic DNA was extracted from all the blood samples, and using a specific primer all the coding ITGB2 gene exons were PCR amplified.RESULTS: The amplified products were sanger sequenced. DNA sequencing analysis revealed a nonsense mutation c.186C > A, p.(Cys62*) in exon four and a missense mutation c.382G>T, p.(Asp128Tyr) in exon five of the gene. The mutation is segregating in autosomal recessive pattern in the family.CONCLUSION: Recurrent mutations on a specific locus (gene) changes the allele frequency from a healthy allele to a disease allele and hence play role in new genotype. This research study demonstrates the allelic heterogeneity of the ITGB2 gene in Pakistani patients diagnosed with LAD1. The research findings in the present study suggest that every population should develop national registry of patients suffering from primary immune deficiencies and a mutation database for rare genetic disorders. This will facilitate early diagnosis and genetic counseling to the patient family.